Occurrence of COVID‐19 in priority groups receiving ChAdOx1 nCoV‐19 coronavirus vaccine (recombinant): A preliminary analysis from north India. Issue 1 (12th September 2021) - Kaur, Upinder; Bala, Sapna; Ojha, Bisweswar; Jaiswal, Sumit; Kansal, Sangeeta; Chakrabarti, Sankha S.
Abstract: The ChAdOx1 nCoV‐19 vaccine (Oxford University‐Astra Zeneca) has demonstrated nearly 70% efficacy against symptomatic COVID‐19 in trials and some real‐world studies. The vaccine was the first to be approved in India in early January 2021 and is manufactured by the Serum Institute of India. Favorable short‐term safety data of the vaccine in India in a real‐world setting has been recently demonstrated. Here, we report secondary objective (COVID‐19 occurrence) measures of the same ongoing prospective observational study in prioritized recipients of the vaccine. The findings are based on participants who could complete at least 2 months of follow‐up ( n  = 1500; female/male: 472/1028; mean age: 38.8 years). Laboratory confirmed SARS‐CoV‐2 infection was observed in 27/65 participants (41%) who received a single dose and 271/1435 (19%) who received both doses. Specifically, among doctors, 18/27 (66.7%) one dose recipients and 131/377 (34.7%) fully vaccinated developed SARS‐CoV‐2 infection. The majority of the cases were mild in all groups, and most were breakthrough infections. The occurrence of "severe" COVID‐19 was 7.7 times lower (0.4%) in fully vaccinated participants compared to partially vaccinated (3.1%). Four deaths were observed in the study. One of the four deaths was due to sepsis, two due to unspecified cardiac events, and one due to unspecified post‐COVID‐19 complications. The results of this preliminary analysis necessitate vigorous research on the performance of vaccines against variants, optimal timing of vaccination, and also optimal timings of effectiveness studies to guide future vaccination policy. Highlights: High rate of breakthrough infections may be observed after both doses of ChAdOx1 based COVID‐19 vaccine, due to strain‐specific and other factors Most breakthrough infections are mild Future research is needed to determine real‐world efficacy as well as safety of COVID‐19 vaccines in diverse geographical regions